GAME-BASED VOCABULARY LEARNING TO KINDLE LEXICAL ACCESS AND VOCABULARY RETRIEVAL IN SECOND LANGUAGE LEARNING - Dharma Raja, B. William; Prabha, D. Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Human beings communicate with others through a language in the form of words, which is stored in the mental lexicon. The stored lexical entries from the mental lexicon are retrieved through lexical access. In the case of learning English as a second language, children face a challenge with fluency, as their mental lexicon has a limited vocabulary size. Children often struggle to expand their academic vocabulary knowledge due to a lack of familiarity with the words in their daily usage. Lacking fluency and effective teaching methods daunt the English language learner's interest in learning novel vocabulary. To stimulate their interest, they need to be motivated through unique methods; one among them is game-based vocabulary learning. This paper tries to put forward the importance and ways for increasing the accumulation of vocabulary in the mental lexicon and access the vocabulary glibly through game-based vocabulary learning while communicating in English as a second language.